Parallel evolution of angiosperm‐like venation in Peltaspermales: a reinvestigation of Furcula - Mario Coiro (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Stephen McLoughlin (Department of Palaeobiology, Swedish Museum of Natural History); Margret Steinthorsdottir (Department of Bioinformatics and Genetics, Swedish Museum of Natural History); Vivi Vajda (Department of Palaeobiology, Swedish Museum of Natural History); Dolev Fabrikant (The Hebrew University of Jerusalem); Leyla J. Seyfullah (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (New Phytologist, 2024)
The abstract is available here: https://uscholar.univie.ac.at/o:2068100 The abstract is available here: https://uscholar.univie.ac.at/o:2068100